2014
DOI: 10.1073/pnas.1408090111
|View full text |Cite
|
Sign up to set email alerts
|

A family of starch-active polysaccharide monooxygenases

Abstract: The recently discovered fungal and bacterial polysaccharide monooxygenases (PMOs) are capable of oxidatively cleaving chitin, cellulose, and hemicelluloses that contain β(1→4) linkages between glucose or substituted glucose units. They are also known collectively as lytic PMOs, or LPMOs, and individually as AA9 (formerly GH61), AA10 (formerly CBM33), and AA11 enzymes. PMOs share several conserved features, including a monocopper center coordinated by a bidentate N-terminal histidine residue and another histidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
222
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(230 citation statements)
references
References 45 publications
5
222
0
3
Order By: Relevance
“…Fungal LPMOs that oxidize cellulose belong to AA9 (formerly GH61) (315,319,321), and more recently a fungal LPMO that oxidizes chitin has been characterized for AA11 (322). In addition, an LPMO active on starch was reported and is now classified as AA13 (323). Chitin and cellulose are ␤(1¡4)-linked polymers with flat molecular surfaces, whereas starch contains ␣(1¡4) linkages (amylose) and ␣(1¡6)-linked side chains (amylopectin).…”
Section: Cazymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal LPMOs that oxidize cellulose belong to AA9 (formerly GH61) (315,319,321), and more recently a fungal LPMO that oxidizes chitin has been characterized for AA11 (322). In addition, an LPMO active on starch was reported and is now classified as AA13 (323). Chitin and cellulose are ␤(1¡4)-linked polymers with flat molecular surfaces, whereas starch contains ␣(1¡4) linkages (amylose) and ␣(1¡6)-linked side chains (amylopectin).…”
Section: Cazymesmentioning
confidence: 99%
“…LPMOs have been shown to oxidize either the C-1 or C-4 atom of the ␤(1¡4) glycosidic bond on the surface of chitin or cellulose (315,317,318) and C-1 of starch (323), resulting in the cleavage of this bond and the creation of new chain ends that can be subsequently processed by hydrolytic chitinases and cellulases. Already before the mode of action of LPMOs was recognized, it was shown that the addition of these proteins (i.e., GH61 and CBM33 proteins) to enzyme mixtures significantly enhanced the degradation of cellulose and chitin in synergism with the respective hydrolases (324)(325)(326).…”
Section: Cazymesmentioning
confidence: 99%
“…These enzymes are the lytic polysaccharide monooxygenases (LPMOs), which are currently sequenceclassified into four families in the CAZy database (www.CAZy.org) -AA9 and AA10 (previously GH61 and CBM33 respectively) 3 , as well as the more recent AA11 4 and AA13 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it was noted that the abundance, the large sequence variation, and the varying domain composition of LPMOs encoded in the genomes of biomass-degrading microorganisms suggest that some of these enzymes could have other substrates (1). Indeed, three studies published in 2014 have broadened the LPMO paradigm by demonstrating cleavage of soluble cellodextrins (13), hemicelluloses with ␤(134)-glucan backbones (14), and even starch (15). Based on sequence characteristics, LPMOs are currently categorized in auxiliary activity (AA) families 9 -11 and 13 of the CAZy database (16).…”
mentioning
confidence: 99%